Bamboo Waste Management Model to Strengthen the Ban Pho Ngam Community, Prachinburi Province - Rakbumrung, Vipawadee; Pantamanatsopa, Pruttipong; Buaboon, Sirichon; Sungsanit , Kullawadee; Ariyawiriyanan, Warunee (Area Based Development Research Journal, 2023)
Ban Pho Ngam Community in Prachantakham district, Prachinburi province grows bamboo and has acquired local wisdom in producing bamboo handicrafts. Throughout the manufacturing process, the community handicrafts generate much bamboo waste such as bamboo scraps, bamboo stumps, and poor-quality bamboo stick scraps. In the past, the community used a variety of techniques to dispose of bamboo waste, including crushing and mixing with soil for fertilizer, but most of the waste will be eradicated through the burning method. This had a pollution effect and would impact community health in the long run. This research aims to find a model for bamboo waste management to enhance the Ban Pho Ngam community through participatory engagement procedures. There are 1) visiting and investigating local concerns, concepts, and identities; 2) designing a management model for bamboo waste; 3) educating the classification of the types and sizes of waste bamboo powder; 4) mixing the bamboo waste with thermoplastic starch to generate a product; and 5) establishing industry-community links. The result showed that the community can minimize bamboo waste by classifying the shape and size of bamboo fragments and then transferring them to a private manufacturer to make products. While bamboo is processed into biodegradable food containers based on easy-to-form thermoplastic starch, the Ban Pho Ngam community’s goal for the eco-product from bamboo waste is realized. The product accommodates both local use and sales. Apart from the container, bamboo waste fragments for sale are made available in two sizes – 0.5 and 1.0 mm. The sales of this type of waste generate an income of 10 baht/kg whereas the factory can reduce costs in ordering bamboo waste by about 3,000 baht/month. The community has income from the bamboo waste while also reducing the quantity of bamboo waste in the area. The product has a hardness of 25.3-28.7 Shore D, and an impact strength of 4.0–4.5 J/m. Therefore, Ban Pho Ngam is encouraged to establish a new value chain for bamboo waste in two aspects: 1) emerging communities for new jobs in bamboo waste sorting and sale to the commercial sector; 2) communities creating environmentally friendly food containers for local consumption and sale. In both cases, the process of transforming waste into new products has the effect of changing people’s mindsets. It provides an extra source of income while also reducing the quantity of bamboo waste in the area. In conclusion, the waste management model may be applicable in other communities.